Simplications Documentation Format of the Midwifery Care SOAP - Romlah, Romlah; Sari, Anjelina Puspita; Anita, Theresia (Jurnal Ilmiah Kesehatan (JIKA), 2024)
The recording format used by midwives in midwifery services is often not in accordance with the midwife's procedures and authority. Recording formats are often complicated, time consuming, and filled out incompletely. This research aims to determine the effectiveness of the SOAP documentation format for midwifery care. This type of comparative design research on 52 samples uses the old SOAP assessment format sheet and SOAP simplifications, research implementation February-November 2023. The data analysis technique uses Paired Sample T-Test analysis. The results of statistical tests show that there is a difference in the length of time for filling out the old SOAP and the simplified SOAP, seen from the competence of the subject who are competent in recording the simplified SOAP. It is hoped that this research will become a reference for midwifery lecturers and students in compiling documentation according to standards, considering that the results show that a simplified format is more effective, efficient and in line with midwife competencies.